2021
DOI: 10.3389/fonc.2021.774413
|View full text |Cite
|
Sign up to set email alerts
|

Fractal-Based Radiomic Approach to Tailor the Chemotherapy Treatment in Rectal Cancer: A Generating Hypothesis Study

Abstract: IntroductionThe aim of this study was to create a radiomic model able to calculate the probability of 5-year disease-free survival (5yDFS) when oxaliplatin (OXA) is or not administered in patients with locally advanced rectal cancer (LARC) and treated with neoadjuvant chemoradiotherapy (nCRT), allowing physicians to choose the best chemotherapy (CT) regimen.MethodsLARC patients with cT3–4 cN0 or cT1–4 cN1–2 were treated according to an nCRT protocol that included concomitant CT schedules with or without OXA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…One of the future directions of this work once reaching a significant number of patients will be that of carrying out a dedicated analysis on subpopulations treated with different adjuvant chemotherapy schemes, with the aim of obtaining indications on the optimal chemotherapy approach on the basis of radiomics information extracted from MRI, as already demonstrated on similar experiences carried out on 1.5-T MR images ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the future directions of this work once reaching a significant number of patients will be that of carrying out a dedicated analysis on subpopulations treated with different adjuvant chemotherapy schemes, with the aim of obtaining indications on the optimal chemotherapy approach on the basis of radiomics information extracted from MRI, as already demonstrated on similar experiences carried out on 1.5-T MR images ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cusumano et al selected only one feature (fractal dimension [FD]) on T2WI associated with the optimal concomitant chemotherapy regimen (with or without oxaliplatin) for stage III LARC. This study suggested that patients with maxFD 30%–50% > 1.6 should be treated with oxaliplatin (OXA) for higher disease‐free survival for 5 years (AUC, 0.67 vs. 0.75) 51 . Hence, radiomics has the potential to help individual treatment making by choosing patients who may benefit from adjuvant chemotherapy and allowing physicians to select the optimal chemotherapy management.…”
Section: Clinical Applications Of Ai In Rc Based On Mrimentioning
confidence: 99%